PENGAJARAN AGAMA MELALUI PENDEKATAN MULTIKULTURAL STRATEGI DAN PELUANG - Tri Astuti Kumaraningtyas (FASHLUNA, 2021)
Multicultural education is an educational system. Trying to reduce social inequality, social class, by introducing social jealousy and one of the directions of socialization is unity. Therefore it is necessary in Islamic education institutions to implement a teaching-oriented system, to build a sense of diversity in life. Some very strategic educational programs. Fostering a sense of diversity is: school education must equip students or learners, a framework allows. Gather and understand the knowledge obtained from the environment. The idea of multiculturalism is not difficult, because teaching each other in Islam respects and recognizes the existence of others. Differences in color, language and culture must be accepted. Be positive, a sign of the greatness of Allah SWT. For this, the attitude that Muslims need to adopt. In dealing with diversity and difference, look at it positively.